Islamic Banking - Bláha, Jakub; Vacek, Vladislav; Zetek, Pavel; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2014)
The aim of this bachelor thesis is to introduce the Islamic banking. Describing historical and religious background of Islam, the Islamic banking and Shari'ah law. Then presenting financing techniques used in the Islamic banking. Eventually describing and analysing the Islamic banking in Malaysia. Comparison between the Islamic banking and the conventional banking is given throughout the bachelor thesis.
Vedoucí práce: Vladislav Vacek
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor bakal. práce]; bakalářské práce; bachelor's theses